Pematuhan pembayaran cukai pada alaf baru di Indonesia - Teng, Sauh Hwee (2023)
Indonesia has the lowest tax ratio when compared to other Asian nations. Taxpayer’s attitude and non-compliance with paying taxes are caused by the low tax percentage. This research aims to investigate the behaviour of taxpayers’ attitude obedience to their tax compliance attitude. Factors that influence the behaviour of tax compliance attitude in this research are internal factors like taxpayer’s knowledge, taxpayer’s understanding, taxpayer’s anxiety, as well as external factors like officers’ quality service, tax rate, and tax penalty. In addition the mediation factors perceptions of taxpayer satisfaction and t h e government spending system. This research advances the previous tax compliance model. The population analyzed in this study consists of registered Indonesian taxpayers. This research employs the Krejcie and Morgan sampling method and samples 380 respondents. The method of data analysis used in this research was by convergent validity partial least square test. The result of this research indicates that taxpayers’ understanding, officers' quality services, taxpayers’ satisfaction and the government spending system influence the taxpayer’s compliance. The taxpayer’s understanding, and tax penalties influence the taxpayer’s satisfaction. The taxpayer’s knowledge, and tax rate influence the government spending system. This research concludes that taxpayers will be more likely to obey the tax obligators if they understand taxes, receive good quality tax service from tax officers, and are more satisfied with the government’s transparency. They will also be more satisfied if they understand taxes and tax penalties.